2021
DOI: 10.3389/fnins.2021.785995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noradrenaline on the Facial Stimulation-Evoked Mossy Fiber-Granule Cell Synaptic Transmission in Mouse Cerebellar Cortex

Abstract: Noradrenaline is an important neuromodulator in the cerebellum. We previously found that noradrenaline depressed cerebellar Purkinje cell activity and climbing fiber–Purkinje cell synaptic transmission in vivo in mice. In this study, we investigated the effect of noradrenaline on the facial stimulation-evoked cerebellar cortical mossy fiber–granule cell synaptic transmission in urethane-anesthetized mice. In the presence of a γ-aminobutyrateA (GABAA) receptor antagonist, air-puff stimulation of the ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Noradrenaline (NE) is a sort of crucial biogenic neurotransmitter in the human body, and its dysregulation is tightly involved in various neurodegenerative diseases, such as Alzheimer’s, Parkinson’s, pheochromocytoma, etc. , whose level is crucial for monitoring and diagnosing diseases. , Moreover, noradrenaline is currently the most commonly used vasopressor agent in clinical applications for treating septic shock, cardiogenic shock, and hypovolemic shock; thus, the injected dose influences the drug effects. , Therefore, the detection of noradrenaline possesses important significance for clinical diagnosis and pharmaceutical quantification. Based on the superefficient and stable ECL behavior (Figure A) of the β-CD-Au NCs/TEA system and the effective quenching performance of NE toward the ECL system, a sensitive and convenient “signal off” sensor for the detection of NE was constructed by adding a series of concentrations of NE into the detection solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noradrenaline (NE) is a sort of crucial biogenic neurotransmitter in the human body, and its dysregulation is tightly involved in various neurodegenerative diseases, such as Alzheimer’s, Parkinson’s, pheochromocytoma, etc. , whose level is crucial for monitoring and diagnosing diseases. , Moreover, noradrenaline is currently the most commonly used vasopressor agent in clinical applications for treating septic shock, cardiogenic shock, and hypovolemic shock; thus, the injected dose influences the drug effects. , Therefore, the detection of noradrenaline possesses important significance for clinical diagnosis and pharmaceutical quantification. Based on the superefficient and stable ECL behavior (Figure A) of the β-CD-Au NCs/TEA system and the effective quenching performance of NE toward the ECL system, a sensitive and convenient “signal off” sensor for the detection of NE was constructed by adding a series of concentrations of NE into the detection solution.…”
Section: Resultsmentioning
confidence: 99%
“…Noradrenaline (NE) is a sort of crucial biogenic neurotransmitter in the human body, and its dysregulation is tightly involved in various neurodegenerative diseases, such as Alzheimer's, Parkinson's, pheochromocytoma, etc., whose level is crucial for monitoring and diagnosing diseases. 43,44 Moreover, noradrenaline is currently the most commonly used vasopressor agent in clinical applications for treating septic shock, cardiogenic shock, and hypovolemic shock; thus, the injected dose influences the drug effects. 45,46 Therefore, the detection of noradrenaline possesses important significance for clinical diagnosis and pharmaceutical quantification.…”
Section: Investigation Of β-Cd Ligand-based Shielding Effect and Supe...mentioning
confidence: 99%
“…NA depresses climbing fiber-PC and MF-GC synaptic transmission via α2-ARs 26 28 , and therefore we applied the α2-AR antagonist yohimbine (100 µM) to determine whether NA can inhibit MLI-PC synaptic transmission through activation of α2-ARs. The results showed that application of yohimbine completely abolished the inhibitory effect of NA on P1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, NAergic fibers form varicosities near the dendrites of PCs 38 , which indicates that NAergic afferents are critical for the regulation of PC activity and synaptic transmission in the cerebellar cortex 9 , 11 . Electrophysiological studies in living animals have demonstrated that NA depressed neuronal activity in the cerebellar cortex via the activation of α2-ARs 26 , 27 and also inhibited facial stimulation-evoked MF-GC synaptic transmission 28 . The present results showed that cerebellar surface micro-application of NA inhibits either facial stimulation- or electric stimulation-evoked MLI-PC synaptic transmission in a concentration-dependent manner, accompanied by a significant increase in the P2/P1 ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation